Self‐assembled organic/metal ion nanohybrids for theranostics. Issue 2 (2nd May 2020) - Zhang, Kai; Zhao, Nana; Xu, Fu‐Jian
Abstract: Owing to their remarkable physicochemical and favorable biological properties, self‐assembled organic/metal ions nanohybrids show great potential for constructing multifunctional nanoplatforms of cancer theranostics. By tailoring the structural components of organic blocks and metal ions, various nanoplatforms with integrated properties can be manufactured. These nanoplatforms offer different capacities, including high loading effect, facile modification/functionalization, and excellent biocompatibility, which are beneficial for applications in bioimaging and cancer treatments. This review focuses on the design, fabrication, properties of organic/metal ions nanohybrids, and their applications in biosensing, bioimaging, therapy, and bioimaging‐guided therapy of cancer. Various research works related to organic/metal ions nanohybrids toward cancer theranostics are highlighted. By presenting and summarizing these research works and discoveries, the species of organic blocks are classified into synthetic organic molecules and biomolecules. Besides, the intrinsic properties and synergistic characteristics of organic blocks and metal ions are also discussed. The prospects and challenges for future researches in this field are also proposed. Abstract : Self‐assembled organic/metal ions nanohybrids composed of designable organic blocks and multifarious metal ions via coordinated connection have a great potential for cancer theranostics, due to their remarkable physicochemical properties and favorable biological capacities. In this review, the authors introduce the design and fabrication of organic/metal ions nanohybrids, as well as their applications in biosensing, bioimaging, treatments, and bioimaging‐guided therapy of cancers.